Retrospective Hospital Based Study Of Carotid Doppler Findings in Acute Ischemic Stroke Patients With Diabetes Mellitus in A Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medicine, 2022)
Background: To evaluate Doppler study findings of Neck Vessels findings in ischemic stroke patients with Diabetes Mellitus admitted in a tertiary hospital.Methods: This cross-sectional descriptive study was carried on 96 diabetic subjects with ischemic stroke aged 40-87 years admitted in the Department of Neurology, BIRDEM general Hospital, over a period of six months.Results: The mean age was 63.45 years with standard deviation of mean (SD) ±19.65 years and their age ranged from 40 to 87 years. Out of 96 subjects 64 (66.67%) were male and rest 32 (33.33%) were female. Study subjects had hypertension (75%), Dyslipidemia (57.29%), history of smoking (53.12%) and alcoholism (1.04%) as common risk factors of ischemic stroke. It was revealed that mean fasting blood glucose (FBG), after meal blood glucose (AG) and HbA1C% level was 11.61 mmol/l, 16.53 mmol/l and 9.3% respectively. Mean ± SD total cholesterol level was 245±102.4 mg/ dl. Mean (± SD) triglyceride, HDL and LDL levels were 362 (±265) mg/dl, 35.83 (±13.72) mg/dl and 135 (±49.43) mg/dl respectively. It was observed that majority 85 (88.54%) of the subjects presented with hemiplegia after acute stroke. Other common clinical presentations were aphasia 64 (66.67%), headache 33 (34.37%), convulsion 20 (20.83%), vomiting 12(12.50%) and cranial nerve palsy 15 (15.62%). Atherosclerotic change (60.41%) in the arterial wall was most common finding in doppler study among the study subjects. Plaques were also found and most (29.17%) of the plaques was homogenous. Calcified plaque was seen in 4.17% cases. Complete occlusion of internal carotid arterial flow was found on both right (2.08%) and left (3.12%) sides. 3.12% subjects were hemodynamically normal on Doppler study.Conclusion: The majority of the Diabetic subjects with ischemic stroke had atherosclerotic change in carotid arterial systems with presence of plaque in this study.Bangladesh J Medicine 2022; 33: 31-35